PARENTING PADA PASANGAN KELUARGA MUSLIM MILENIAL DI ERA CIVIL SOCIETY 5.0 (Studi Kasus di Kota Samarinda) - Fifindari, Asmaul (Counseling Milenial (CM), 2023)
This research aims to gain an in-depth understanding of how millennial Muslim families integrate religious values, technology, and the dynamics of modern societal trends in child-rearing. Employing a qualitative methodology with a case study approach, data collection involved observing the behaviors of millennial Muslim families and conducting interviews with selected families engaged in child-rearing. The findings reveal that these families face complex challenges in the era of Civil Society 5.0, underpinned by a strong commitment to Islamic teachings. While acknowledging the potential of technology, these families are aware of the risks associated with excessive screen time. Proactive strategies, such as limiting technology use and active supervision, are implemented to maintain a balance. Despite navigating the dynamics of modern societal trends, these families are not only responsive but also actively guide their children with flexibility in upholding traditional values. The strategic measures taken lay a robust foundation for child-rearing in the age of technology. This research provides valuable insights for parenting guidelines for millennial Muslim families, emphasizing the importance of maintaining a balance between tradition and innovation in educating children in the modern era.